Effect of short‐chain fatty acids on triacylglycerol accumulation, lipid droplet formation and lipogenic gene expression in goat mammary epithelial cells. (24th August 2015) - Sun, Yuting; Luo, Jun; Zhu, Jiangjiang; Shi, Hengbo; Li, Jun; Qiu, Siyuan; Wang, Ping; Loor, Juan J.
Abstract: Short‐chain fatty acids (SCFAs) are the major energy sources for ruminants and are known to regulate various physiological functions in other species. However, their roles in ruminant milk fat metabolism are still unclear. In this study, goat mammary gland epithelial cells (GMECs) were treated with 3 mmol/L acetate, propionate or butyrate for 24 h to assess their effects on lipogenesis. Data revealed that the content of triacylglycerol (TAG) and lipid droplet formation were significantly stimulated by propionate and butyrate. The expression of FABP3, SCD1, PPARG, SREBP1, DGAT1, AGPAT6 and ADRP were upregulated by propionate and butyrate treatment. In contrast, the messenger RNA (mRNA) expression of FASN and LXRα was not affected by propionate, but reduced by butyrate. Acetate had no obvious effect on the content of TAG and lipid droplets but increased the mRNA expression of SCD1 and FABP3 in GMECs. Additionally, it was observed that propionate significantly increased the relative content of mono‐unsaturated fatty acids (C18:1 and C16:1) at the expense of decreased saturated fatty acids (C16:0 and C18:0). Butyrate and acetate had no significant effect on fatty acid composition. Overall, the results from this work help enhance our understanding of the regulatory role of SCFAs on goat mammary cell lipid metabolism.